Design and development of a grating machine for wet sago starch production - Wan Azman, Wan Mohd Fariz (2020)
This thesis describes a study on the design, fabrication and testing of a prototype grating machine for wet sago starch production. In order to extract the starch, the mechanical method is required to break the trunk and producing fine grated sago. The more refined the grated sago produce, the more sago starch can be dissolved in water during the extraction process. In this case, it was reported that 65.7% of sago starch remained inside the residue. A new technology has been developed to overcome the issue. The determination of physical and mechanical properties of sago trunk was conducted as a prerequisite for designing process. A primarily study was conducted on Handheld Chainsaw, Roller Grater, Coconut Husk Decorticator and Coconut Grinder to determine the grating speed, grated sago size distribution and grating contact area. The result shown that the hand chainsaw produced the highest percentage of finer grated sago (56.80%: X≤0.85 mm) and the lowest teeth contact surface area of 4 mm2. However, it has the lowest capacity. A further study was conducted to determine the effect of grated sago sizes on starch recovery at different steeping periods and. As a result, a substantial amount of starch could be recovered from grated sago by reducing the grated size at X<0.30 mm which was up to 58% of the extraction efficiency. The increment of the steeping period from 5 min up to 24 hours increased the starch recovery. However, a longer steeping period showed an insignificant difference (P>0.05). A new concept of sago grater was designed and developed. Initially, an assessment of sago grating machine design requirement was conducted using surveys. All the needs and goals were divided into several sub-objectives. The sub-objective was converted into functions modeling to generate sub-functions and then select the appropriate technology. A Morphological Chart was used to produce 6 complete system concepts. The selection of complete system concepts was based on matrix assessment and detail design of concept was generated for the fabrication process. The newness of sago grating machine has the advantages over the existing machines. It does not require conducting a debarking process (20 minutes per log). The machine has the capability to adjust the feeding height (0 cm to 5 cm) according to the sago trunk diameter size which is minimizing the losses during the grating process. The design novelty, the grater disc has ability of adjusting the disc diameter size (40 cm to 48 cm), which is no need to be made in various of sizes and each single part of grater teeth can be replaced to reduce the maintenance costs. The grating capacity was 45.9 kg/min with a total starch recovery percentage was 19.86±0.14% and at 47.97%.of extraction efficiency.